Different solid forms for optimizing route of administration of the herpes drug Pritelivir. Issue 11 (9th September 2019) - Ruebsamen-Schaeff, Helga; Buschmann, Helmut
Abstract : In depth knowledge of the physicochemical properties of different salt forms and respective solvates/hydrates has a significant impact on the pharmaceutical dosage form. Abstract : Pritelivir (AIC316, BAY 57-1293) was discovered as a highly potent drug against herpes simplex viruses with a novel mode of action, i.e. inhibition of the viral helicase–primase. A side by side comparison of the oral form against Valtrex™ in patients with genital herpes, showed superiority in phase II testing for Pritelivir. A number of different solid forms have been generated for additional, e.g. systemic, or topical applications.